Implementation of Fuzzy-PID in Flow Rate Regulation System in Wastewater Treatment - Trinh Luong Mien; Hamza Iftikhar; Khaled Mustafa; Abdulgani Albagoul; Mustafa Salem Ahmed (Tinta Emas Publisher, 2025)
Seeing the situation of water availability this is beginning to decrease, it's miles very critical to do water remedy in advance than water this is healthy for use. The layout of the device includes a herbal clear out out and a pH measuring device. In this examine, the water clear out out is designed in a family scale with the manage of water glide withinside the filtration process. The manage approach used on this examine is fuzzy PID. Fuzzy PID is used to control the water motion which enters the clear out out via way of means of adjusting the pump velocity that stimulated via way of means of the purity of the filtered water. meanwhile, the bushy common sense is used to generate the detail of Kp, Ki, and Kd withinside the PID manage with the enter that includes an blunders and its alternate. In this examine, it's miles acknowledged that the glide fee of the water flowing is be capable of have an effect on the price of water purity that's generated from the filtration process. The glide fee will alternate from 872 L/H into 414 L/H whilst the purity price is reduced from 94% into 90%. then, the purity price will boom from 90% into 94%.